The Influence of Store Atmosphere and Price on Sales Levels Through Purchasing Decisions As A Mediator - Tanjung, Ulil Amri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
This study aims to examine how much influence the store atmosphere and prices have on the level of sales of coffee from Hati Pariaman through purchasing decisions as an intervening variable. Methods of data collection through surveys and distributing questionnaires, with a sample of 100 respondents. The analytical method used is SEM analysis using smartpls. The research results obtained based on hypothesis testing obtained that there is a significant influence of store atmosphere on purchasing decisions. There is a significant effect of prices on purchasing decisions. There is a significant influence store atmosphere on the level of sales. There is a significant effect of prices on the level of sales. There is a significant influence of purchasing decisions on the level of sales. Purchase decisions mediate the effect of store atmosphere on sales levels. Purchasing decisions mediate the effect of prices on sales levels.